PENERAPAN FONETIK AKUSTIK DALAM BACAAN MAD ALQURAN (STUDI KASUS PADA QIRAAT QARI INTERNASIONAL) - Muflihana Dwi Faiqoh, Moh. Masrukhi (Arabic Literature Department, 2019)
The time duration is one of the important acoustic features discussed among the researchers. This article presents the results of a study of variation and duration of madd (long vowel). The data were obtained by downloading of two Quran reciterswho are Muammar Zainal Asyiqin and Maria Ulfahfrom the website.To investigate the duration of the types of madd, it uses an acoustic phonetics approach andto measure the acoustic duration of these madd, it employs the computer program ‘Praat’.Among the most important results, it is noted that Maria has the longer duration than Muammar does. Furthermore, the investigation of madd duration is addressed well, followed by the analysis for each madd.